2018
DOI: 10.3906/bot-1707-29
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to the taxonomy of Lactuca (Asteraceae) in Turkey

Abstract: Morphological measurements and micromorphological photographs were done with a Leica S6D microscope. Herbarium specimens were photographed with a Canon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 5 publications
(7 reference statements)
0
12
0
Order By: Relevance
“…This lead to infer that the accession from Turkey might be subjected to a natural mutation or a sort of unintended domestication. Although Güzel et al (2018) observed several samples in the eld and herbaria belonging to L. viminea that easily fell into two distinct subspecies according to their habits and morphological traits, the clustering dendrograms of isozymes and RAPD analyses separated the accessions of L. viminea in one cluster which was inconsistent with their observation. The variation observed by Güzel et al (2018) could be attributed ecogeographical conditions in which the accessions of L. viminea were originated; the conditions that cause a signi cant variation in the phenotypic characters.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This lead to infer that the accession from Turkey might be subjected to a natural mutation or a sort of unintended domestication. Although Güzel et al (2018) observed several samples in the eld and herbaria belonging to L. viminea that easily fell into two distinct subspecies according to their habits and morphological traits, the clustering dendrograms of isozymes and RAPD analyses separated the accessions of L. viminea in one cluster which was inconsistent with their observation. The variation observed by Güzel et al (2018) could be attributed ecogeographical conditions in which the accessions of L. viminea were originated; the conditions that cause a signi cant variation in the phenotypic characters.…”
Section: Discussionmentioning
confidence: 79%
“…Although Güzel et al (2018) observed several samples in the eld and herbaria belonging to L. viminea that easily fell into two distinct subspecies according to their habits and morphological traits, the clustering dendrograms of isozymes and RAPD analyses separated the accessions of L. viminea in one cluster which was inconsistent with their observation. The variation observed by Güzel et al (2018) could be attributed ecogeographical conditions in which the accessions of L. viminea were originated; the conditions that cause a signi cant variation in the phenotypic characters. The clustering dendrogram based on RAPD data indicated a close genetic relationship between L. sativa, L. serriola, L. saligna and L. virosa which was consistent with the phylogenetic trees based on chloroplast DNA sequence comparison (Wei et al 2017), chromosomal studies (Matoba et al 2007), nrITS1 and AFLP ngerprints (Koopman et al 2001).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Lastrucci, G. Ferretti, L. Lazzaro Physalis peruviana is a herbaceous perennial species, which has been very widely introduced across the world from South America as a cultivated plant for its fruit, as a medicinal plant, and as an ornamental (CABI 2018). It is reported as a casual alien in several administrative regions, especially in northern Italy, and as naturalized in Sicilia (Galasso et al 2018 Nomenclature and distribution updates from other literature sources Nomenclature, status, and distribution updates according to Béguinot (1903), Devesa (2007), Kilian et al (2009+), Göktürk and Sümbül (2014), Liu et al (2017), Banfi (2018), Güzel et al (2018), and Martini and Viciani (2018), and corrections to Ga lasso et al (2018) are provided in Supplementary material 1. G. Galasso…”
Section: Bougainvillea Spectabilismentioning
confidence: 99%
“…P.H.Raven, Pavonia hastata Cav. (see also Galasso et al 2017 Nomenclature, status, and distribution updates according to Béguinot (1903), Devesa (2007), Kilian et al (2009+), Göktürk and Sümbül (2014), Liu et al (2017), Banfi (2018), Güzel et al (2018), and Martini and Viciani (2018), and corrections to Ga lasso et al 2018are provided in Supplementary material 1. G. Galasso…”
Section: N Olivierimentioning
confidence: 99%